2003
DOI: 10.1002/ajmg.a.20055
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 27 gene: Chromosomal and molecular location and relationship to Williams syndrome

Abstract: Heat shock protein 27 (HSP27) is one of a number of actin-binding proteins that regulate actin polymerization. Three related HSP27 sequences had previously been mapped to chromosomes 3, 9, and X. We have used fluorescent in-situ hybridization (FISH) to correct and refine the map position of the transcribed HSP27 gene (locus HSPB1) to chromosome 7q11.23. This band also contains the site of the deletion associated with Williams syndrome (WS). To define the relationship between HSP27 and the WS deletion, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 21 publications
(28 reference statements)
0
30
0
1
Order By: Relevance
“…Williams syndrome is caused by deletions at 7q11.23, typically ϳ 1.55 Mb long and affecting ϳ 28 genes. A small proportion of patients have larger deletions [Stock et al, 2003;Ferland et al, 2006;Marshall et al, 2008]. PH has been previously described in association with Williams syndrome in one patient [Ferland et al, 2006].…”
Section: Discussionmentioning
confidence: 85%
“…Williams syndrome is caused by deletions at 7q11.23, typically ϳ 1.55 Mb long and affecting ϳ 28 genes. A small proportion of patients have larger deletions [Stock et al, 2003;Ferland et al, 2006;Marshall et al, 2008]. PH has been previously described in association with Williams syndrome in one patient [Ferland et al, 2006].…”
Section: Discussionmentioning
confidence: 85%
“…Although most individuals with 22q11DS have a similar "common 3 Mb deletion", a minority have other overlapping and non-overlapping 22q11.2 deletions (Amati et al 1999;Saitta et al 2004). In other microdeletion syndromes such as Williams syndrome, some aspects of the phenotype appear related to the length of the deletion (Stock et al 2003). In contrast, most studies of 22q11DS have found no evidence for such an association (Carlson et al 1997;Kurahashi et al 1997;Lindsay et al 1995;Saitta et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Az átlagos deletio nagysága 1,55 Mb (95%-ban), amely 26-28 gén elvesztésével jár [3]. Nagyobb mértékű génvesztés, kö-rülbelül 2-4 Mb deletio már súlyos fenotípus-manifesztációhoz vezet, és igen alacsony kognitív funkciót eredményez [4]. Három gén a WBSCR-régióban -ELN (elasztin), GTF1I (general transcription factor 1), GTF2IRD1 (general transcription factor II-I repeat domain-containing protein 1) -különösen fontos szerepet játszik a WS fenotípusában [5,6].…”
Section: Genetikai Jellegzetességekunclassified